1998
DOI: 10.1029/98je00696
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and persistence of 5‐μm hot spots at the Galileo probe entry latitude

Abstract: Abstract. We present a study on the longitudinal locations, morphology, and evolution of the 5-/xm hot spots at 6.5øN latitude (planetocentric) from an extensive Infrared Telescope Facility-National Science Foundation Camera (IRTF-NSFCAM) data set spanning more than 3 years, which includes the date of the Galileo probe entry. A probabilistic analysis of the data shows that within periods of several months to even more than a year, there are eight or nine longitudinal areas with high likelihood of containing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
80
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 36 publications
11
80
0
Order By: Relevance
“…3 [3]. Interestingly these values are similar to the ones that Ortiz et al [4] found when studying the hot spots movement in the IR. After this we tried to apply the same interpretation to the symmetrical marks appearing in the southern limit of the SEB (7º S).…”
Section: Hot Spotssupporting
confidence: 77%
“…3 [3]. Interestingly these values are similar to the ones that Ortiz et al [4] found when studying the hot spots movement in the IR. After this we tried to apply the same interpretation to the symmetrical marks appearing in the southern limit of the SEB (7º S).…”
Section: Hot Spotssupporting
confidence: 77%
“…Wavenumber IH waves were found at equatorial latitudes at depths between PUH mbar and I bar by several authors (Magalhaes et al, 1989;Orton et al, 1994;Harrington et al, 1996;Deming et al, 1997). The source of the waves is unknown and hypothesis range from vertical propagation of Rossby waves (Orton et al, 1994) and mixed Rossbygravity waves (Deming et al, 1997), to connection with the plumes in the equatorial hot-spots (Ortiz et al, 1998;Showman and Dowling, 2000) or association with deep convective cells (Magalhaes et al, 1989). The near stationary appearance of these waves with respect to system III implies possibly a dynamical link between the interior bulk rotation of the planet (Irwin, 2003).…”
Section: The Thermal Structurementioning
confidence: 99%
“…This result is often used as evidence that the winds are deep, though one should remember that beyond the point that this is just a single measurement, the data only accounts for a depth of ISH km which are no more than H:PP% of the radius of Jupiter. In addition the probe entered in a hot-spot (the equatorial zone is punctuated with 10-13 such S m spots (Ortiz et al, 1998)), which may have anomalous dynamics because of non-zonal motions that have been associated with them .…”
Section: The Wind Structurementioning
confidence: 99%
“…Note that this section does not deal with the trapped equatorial Rossby wave pattern on the NEBs [and its associated hotspots and plumes, Allison, 1990;Ortiz et al, 1998;Showman and Dowling, 2000;Baines et al, 2002;Friedson, 2005;Arregi et al, 2006;Choi et al, 2013].…”
Section: A2 Supplemental S2: Previous Detections Of Mid-neb Wavesmentioning
confidence: 99%